Perlindungan Hukum Gabungan Kelompok Tani (Gapoktan) Tani Maju Terhadap Konsekuensi Perjanjian Lisan Jual Beli Hasil Pertanian Hortikultura di Sidakangen Banjarnegara - Silfia Laelatulsya'diyah; Zeehan Fuad Attamimi; Marsitiningsih Marsitiningsih; Astika Nurul Hidayah (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
This study examines the legal consequences of oral agreements in horticultural produce transactions involving members of the Tani Maju Farmers Group Association (Gapoktan) in Sidakangen Village, Banjarnegara, and analyzes the legal protection available to farmers. The research applied a mixed normative and empirical legal approach. Normative data were derived from legislation, legal doctrines, and literature, while empirical data were obtained through interviews with Gapoktan administrators and members. The findings indicate that oral agreements are legally valid if they satisfy the requirements of Article 1320 of the Indonesian Civil Code. Nevertheless, such agreements often create legal disputes, including delayed payments, unilateral price changes, nonpayment, weak evidentiary strength, financial losses, and declining trust among parties. Preventive legal protection may include legal education, transaction documentation, the use of written or electronic evidence, and strengthening farmers' institutions. Repressive protection can be pursued through litigation or non-litigation dispute resolution mechanisms. The study further reveals that non-litigation approaches, particularly deliberation and family-based negotiation, are more effective in rural communities because they are simpler, faster, less expensive, more flexible, and better at preserving social relationships. Therefore, effective legal protection for farmers depends not only on legal regulations but also on community legal culture, legal awareness, and institutional strengthening of farmers' associations. Keywords: legal protection, oral agreements, farmers group association (Gapoktan), breach of contract, horticulture.